Socioeconomic position and quality of life among older people: The mediating role of social support - Henriques, A (2020)
Social support can obscure social gradients in health, but its role as a mediator between socioeconomic position (SEP) and quality of life (QoL) in older populations remains unknown. We aimed to examine to what extent social support mediates the association between SEP and overall QoL among older adults (aged 60–84 years). We studied a population-based cohort of 585 noninstitutionalized adults in Porto, Portugal, who were evaluated in 2009. Education, occupation, and perceived income adequacy were used as SEP indicators. The WHOQOL-OLD was used to determine overall QoL. Social support was assessed using the Multidimensional Scale of Perceived Social Support. Path analysis was conducted to quantify direct, indirect, and total effects of SEP on QoL. There was a positive total effect of education on QoL (β = 0.28; 95% CI: 0.05–0.48). In this model, we found an indirect effect through social support (β = 0.15; 95% CI: 0.05–0.26), explaining 54% of the pathway between education and QoL. A similar pattern was identified for the association between occupation and QoL. Perceived income adequacy had a total effect of 2.74 (95% CI: 1.68–3.93) on QoL. Although an indirect effect through social support was found (β = 0.98; 95% CI: 0.42–1.55), a direct effect from this variable remained (β = 1.76; 95% CI: 0.65–2.90). Social support can be a mechanism through which SEP impacts the QoL of older people. Strengthening social support ties may attenuate the impact of social inequalities and improve the QoL of this population.